2014
DOI: 10.1590/s1679-45082014rw2785
|View full text |Cite
|
Sign up to set email alerts
|

Devemos tratar febre em doentes graves? Resumo da evidência atual de três ensaios clínicos randomizados

Abstract: Fever is a nonspecific response to various types of infectious or non-infectious insult and its significance in disease remains an enigma. Our aim was to summarize the current evidence for the use of antipyretic therapy in critically ill patients. We performed systematic review and meta-analysis of publications from 1966 to 2013. The MEDLINE and CENTRAL databases were searched for studies on antipyresis in critically ill patients. The meta-analysis was limited to: randomized controlled trials; adult human crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In fact, some studies have suggested that antipyresis in critically ill septic patients may be harmful ( 15 – 17 ). The majority of prior meta-analyses of the effect of antipyretic therapy in the critically ill have not focused on septic patients ( 18 – 20 ). Because antipyretic therapy may impact infected and noninfected patients differently ( 16 ), conclusions from these studies are difficult to interpret.…”
mentioning
confidence: 99%
“…In fact, some studies have suggested that antipyresis in critically ill septic patients may be harmful ( 15 – 17 ). The majority of prior meta-analyses of the effect of antipyretic therapy in the critically ill have not focused on septic patients ( 18 – 20 ). Because antipyretic therapy may impact infected and noninfected patients differently ( 16 ), conclusions from these studies are difficult to interpret.…”
mentioning
confidence: 99%